2007
DOI: 10.1002/dneu.20511
|View full text |Cite
|
Sign up to set email alerts
|

RNA transport and localized protein synthesis in neurological disorders and neural repair

Abstract: Neural cells are able to finely tune gene expression through post-transcriptional mechanisms. Localization of mRNAs to subcellular regions has been detected in neurons, oligodendrocytes, and astrocytes providing these domains with a locally renewable source of proteins. Protein synthesis in dendrites has most frequently been associated with synaptic plasticity, while axonally synthesized proteins appear to facilitate pathfinding and injury responses. For oligodendrocytes, mRNAs encoding several proteins for my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 182 publications
0
75
0
Order By: Relevance
“…Protein synthesis plays a critical role in both injury signaling (16,(35)(36)(37) and the formation of new growth cones during regeneration (38). Several proteins translated in peripheral neurons after injury, including vimentin and importin ␤, have been shown to be critical for regeneration (16).…”
Section: Discussionmentioning
confidence: 99%
“…Protein synthesis plays a critical role in both injury signaling (16,(35)(36)(37) and the formation of new growth cones during regeneration (38). Several proteins translated in peripheral neurons after injury, including vimentin and importin ␤, have been shown to be critical for regeneration (16).…”
Section: Discussionmentioning
confidence: 99%
“…Because all of the necessary molecular components for protein translation exist in peripheral axons (55,56), the accumulated axonal NaV1.8 mRNA may, in part, contribute to the increased functional expression of NaV1.8 in the injured nerve. The present study further demonstrated that injection of shRNA3 achieved a normalization of SNE-induced NaV1.8 mRNA in the nerve during the time (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Transport of mRNAs and local control of translation in neuronal dendrites are important cellular mechanisms of long-lasting synaptic plasticity and memory (Martin et al, 2000;Sutton and Schuman, 2006;Bramham and Wells, 2007), and the loss of these control mechanisms is implicated in neuronal disorders (Bassell and Kelic, 2004;Wang et al, 2007). Several mechanisms control local translation, using eIF4E-binding proteins, eEF2, the fragile X mental retardation protein (FMRP), and micro-RNAs (Jin et al, 2004;Kelleher et al, 2004;Klann and Dever, 2004;Kindler et al, 2005).…”
Section: Introductionmentioning
confidence: 99%